2020
DOI: 10.14309/ajg.0000000000001050
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture vs Prucalopride for Severe Chronic Constipation: A Multicenter, Randomized, Controlled, Noninferiority Trial

Abstract: INTRODUCTION: This multicenter, randomized, noninferiority trial compared electroacupuncture with prucalopride for the treatment of severe chronic constipation (SCC). METHODS: Participants with SCC (≤ 2 mean weekly complete spontaneous bowel movements [CSBMs]) were randomly assigned to receive either 28-session electroacupuncture over 8 weeks with follow-up without treatment over 24 weeks or prucalopride (2 mg/d before breakfast) over 32 weeks. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 49 publications
1
33
1
Order By: Relevance
“…[ 19 ] Acupuncture has been proven to be noninferior to prucalopride in relieving severe chronic constipation in a recent study. [ 20 ] However, acupuncture for constipation can be performed only in specialist clinics, making it inconvenient for the patient. Both acupuncture and acupressure are based on meridian theory in Chinese medicine and influence the flow of qi by stimulating acupoints.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Acupuncture has been proven to be noninferior to prucalopride in relieving severe chronic constipation in a recent study. [ 20 ] However, acupuncture for constipation can be performed only in specialist clinics, making it inconvenient for the patient. Both acupuncture and acupressure are based on meridian theory in Chinese medicine and influence the flow of qi by stimulating acupoints.…”
Section: Discussionmentioning
confidence: 99%
“…As an important part of nonpharmacologic therapies, acupuncture treatment has been frequently promoted for managing FC worldwide. Several randomized controlled trials (RCT) have confirmed that acupuncture could increase the frequency of bowel movements, soften stool formation, alleviate defecation straining, and improve the quality of life (12)(13)(14)(15). Clinically, a variety of acupuncture methods are available for FC treatment, including electroacupuncture (EA), auricular acupuncture (AA), warmneedling acupuncture (WNA), fire acupuncture (FA), and moxibustion.…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…Clinically, a variety of acupuncture methods are available for FC treatment, including electroacupuncture (EA), auricular acupuncture (AA), warmneedling acupuncture (WNA), fire acupuncture (FA), and moxibustion. Recently, Liu et al found that the effectiveness of EA was non-inferior to prucalopride in relieving severe chronic constipation (15). A comparison between AA and usual care demonstrated a significant patient preference for AA (16).…”
Section: Description Of the Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely used for treating gastric disorders in clinical practice as a potentially effective therapy. Recent evidence indicated that acupuncture was noninferior to prucalopride for functional constipation with fewer adverse effects [ 13 ]. Considering the particularity of schizophrenic patients, whether acupuncture is efficient for treating antipsychotic-related constipation remains unknown.…”
Section: Introductionmentioning
confidence: 99%